Optimizing Energy Utilization in Unequally Spaced Linear Array for Smart Antenna - Fajemilehin, T. O.; Opadiji, J. F.; Olatunji, S. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
Radiation in the form of unwanted patterns, energy wastage and reduction is caused by high side lobe levels in a radiation pattern. This, in turn, affects the overall performance of the antenna. The purpose of this work is to improve the performance of a smart antenna by optimizing the radiation pattern using the genetic algorithm. Optimal antenna parameters that would minimize side lobe level were obtained using genetic algorithm. Simulations were carried out to determine the impact of the increase in inter-element spacing on array factor and beamwidth using the optimal antenna parameters. The optimal arrangement of inter-element spacing and number of elements in unequally spaced antenna elements were then considered. The array factor model for a uniform linear array of elements was used to obtain the optimum weights that would give the desired radiation pattern with reduced side lobe level. Results for the unequally spaced linear arrays revealed that non-tapered arrangement among all the possible configurations gave the best improvement in the side lobe level. The outcome of this improvement is an optimized radiation pattern which is expected to aid the reduction of radiated power wasted in the side lobes of linear arrays in antenna systems.